2011
DOI: 10.1016/j.reprotox.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorous pesticide exposures and sperm quality

Abstract: Many Americans are exposed to low levels of organophosphorous (OP) pesticides. In is unclear whether these exposures impact sperm production. We investigated whether there was an association between urinary OP insecticide metabolites and sperm concentration and motility in newly married men from a rural area of eastern People's Republic of China. Ninety-four cases and 95 controls were included based on their median residual value of sperm concentration and motility after adjusting for relevant covariates. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 24 publications
1
39
0
2
Order By: Relevance
“…Relationships between the persistent organic pollutants (POPs) DDT and HCH and sperm characteristics were found in five studies (Aneck-Hahn et al, 2007; Haugen et al, 2011; Khan et al, 2010; Messaros et al, 2009; Pant et al, 2007). Organophosphates (OP) were shown to be associated with lowered sperm parameters in six of the studies (Hossain et al, 2010; Perez-Herrera et al, 2008; Perry et al, 2007, 2011; Recio-Vega et al, 2008; Yucra et al, 2008). One study found an association between the pesticide abamectin and decreased sperm motility (Celik-Ozenci et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Relationships between the persistent organic pollutants (POPs) DDT and HCH and sperm characteristics were found in five studies (Aneck-Hahn et al, 2007; Haugen et al, 2011; Khan et al, 2010; Messaros et al, 2009; Pant et al, 2007). Organophosphates (OP) were shown to be associated with lowered sperm parameters in six of the studies (Hossain et al, 2010; Perez-Herrera et al, 2008; Perry et al, 2007, 2011; Recio-Vega et al, 2008; Yucra et al, 2008). One study found an association between the pesticide abamectin and decreased sperm motility (Celik-Ozenci et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…They pointed out a disruptive role of pesticides on sex hormones activities, which could lead to secretory dysfunction of male accessory glands (19). Sperm motility decrease was also reported in cases of specific pesticide exposure such as pyrethroids (20), organochlorines (21,22), and organophosphates (23,24), as well as multiple pesticide exposure (25). In a synthesis review of four cross-sectional studies of the INUENDO project assessing the impact of persistent organic pollutants (POPs) on human fertility (26), PCB congener CB-153 blood levels were inversely related to sperm motility and to neutral α-glucosidase activity, a marker of epididymal function.…”
Section: Discussionmentioning
confidence: 98%
“…al., 2008). Organophospates are associated with decreased sperm concentration, ejaculate volume and total sperm count (Perry et al, 2011). Chiu et.…”
Section: Introductionmentioning
confidence: 99%